KINERJA TENAGA MEDIS DALAM MELAYANI PASIEN RUANG KELAS III RUMAH SAKIT BUDI SETIA LANGOWAN KABUPATEN MINAHASA - MANENGAL, FARLY DANIEL; KIYAI, BURHANUDDIN; PALAR, NOVIE (Sam Ratulangi University, 2022)
The performance of the medical personnel is result of the work of everyone who devote ourselves in thehealthcare field and have the knowledge and or skills trough educations in the field of the health of acertain type that requires the authority to perform health efforts. One the of the many health facilitiesare used by the community and has a very important role in providing health services. Is the Hospitalthe purpose of this study to the performance of medical personnel in serving patients in class IIIHospital Budi setia Langowan research using qualitative methods this study uses the theory ofindicator dimensional performance of Lupiyoady Them is the physical evidence of reliability,Responsiveness, Assurance and empathy. This research using observation techniques of interview,observation and document capture. Be able to explain the research problem. The results of this studyconcluded that the performance of medical personnel in serving patients in class III Hospital BudiSetia langowan can be conclude through physical evidence, reliability, responsiveness assurance andempthy make health services for patients in class III Hospital Budi Setia Langowan.Keyword : The performance of the medical personnel